IoT-Enabled Driving License Verification and Alcohol Detection System for Intelligent Vehicle Safety (International Journal of Scientific Research in Science and Technology, 2025)
Road safety remains a global concern due to rising traffic accidents caused by unauthorized driving and impaired conditions. This paper presents an IoT-enabled Driving License Verification and Alcohol Detection System designed to enhance vehicle access control and ensure responsible driving practices. The proposed model integrates a NodeMCU (ESP8266) microcontroller as the central controller, interfacing with an RFID reader for license authentication and an MQ-series alcohol sensor for sobriety detection. Upon detecting an invalid license or alcohol consumption, the system triggers a relay to disable the ignition and may employ a DC gear motor for physical locking of critical components. Real-time system status is communicated via a 16×2 LCD and voice alerts, while a web and Android application provide remote monitoring, data logging, and notifications for authorities or vehicle owners. The system demonstrates a scalable, cost-effective, and non-intrusive solution to reduce road accidents, making it highly suitable for personal vehicles, fleet management, and public transportation systems. By leveraging IoT and automation, the solution contributes to smarter traffic management and safer roads.